A new species of Flabelligeridae (Annelida), Trophoniella radesiensis n. sp., from Tunisia - Chaibi, Marwa; Antit, Mouna; Bouhedi, Marwa; Meca, Miguel A.; Gillet, Patrick; Azzouna, Atf; Martin, Daniel (Zootaxa, 2019)
The family Flabelligeridae was previously represented in Tunisia by four genera including four species: Bradabyssa villosa (Rathke, 1843), Therochaeta flabellata (M. Sars in G.O. Sars, 1872), Pherusa plumosa (Müller, 1776), and Piromis eruca (Claparède, 1869). In this paper we report a fifth genus, Trophoniella, for the first time in Tunisia. The specimens were collected in Radés Station, Gulf of Tunis (Central Mediterranean) and belong to a new species, namely Trophoniella radesiensis n. sp., which is characterized by having: (1) a very smooth tunic, body covered dorsally, ventrally, and laterally by sediment grains (except in the posterior region), and (2) well-developed parapodia showing short neurohooks from chaetiger 6 to 19 and anchylosed neurohooks from chaetiger 20. Based on the 16S, the new species belongs to a low supported Piromis/Trophoniella clade and shows a 16.1% of genetic distance from Trophoniella hephaistos Jimi & Fujiwara, 2016, the single known species of the genus sequenced to date. [Zoobank lsid: urn:lsid:zoobank.org:act:D7C85C70-87FF-4AF4-8599-A8462B3FB8B1]